Processing traits of European catfish (Silurus glanis Linnaeus, 1758) from outdoor flow‐through and indoor recycling aquaculture units. (3rd July 2015) - Adamek, Z.; Grecu, I.; Metaxa, I.; Sabarich, L.; Blancheton, J.‐P.
Summary: The quality of fish cultured using recycling units may differ from that of fish from outdoor farming units due to a range of deviating environmental determinants. This applies not only to flesh quality but also to morphological (processing) traits. This study evaluates processing yields of sibling fish cultured in two different farming units: (i) an outdoor pond aquaculture system with a flow‐through regime (24.6 ± 0.2°C), and (ii) indoor tanks using a recirculation aquaculture system (RAS; 26.0 ± 1.0°C). Clear differences were observed in the most important processing traits, i.e. skinned trunk and fillet yields, which were both significantly higher (P < 0.01) in RAS fish due to significantly smaller (P < 0.05) head weight in fish of the flow‐through system. Skin represented a significantly higher (P < 0.01) proportion of total weight in both RAS males and females. The most obvious difference was in the deposited fat weight, which was significantly higher (P < 0.01) in RAS fish. Visceral fat deposits were significantly higher (P < 0.01) in females and ventral and dorsal fat deposits higher (P > 0.05) in males.